PROJECTS FOR DEVELOPING TOURISM IN UZBEKISTAN - Usmanova Dildora Rustamovna (Web of Journals Publishing, 2024)
In this article we can see observation of the developing projects based on tourism and its impact to Uzbekistan society. Tourism is an information-rich field, in which the collection, transmission, analysis and storage of information play an important role in decision-making at all levels of the field. In this regard, the formation and development of the project is of great importance for tourism activities, in which the latest information and communication technologies are actively used
Keywords: Community based tourism, Association of Private Tourism Organizations of Uzbekistan, the development of the tourism.